Association between Sleep Problems and Psychopathologies among Preschoolers: A Brazilian Cross-Sectional Study - Rafihi-Ferreira, Renatha El; Alckmin-Carvalho, Felipe; Rocha, Marina Monzani da; Campoli, Thiago Soares; Ollendick, Thomas Hubert (Sleep Science, 2024)
Objective To evaluate the relationship between sleep problems and psychopathologies in Brazilian preschool children.Materials and Methods The present is a cross-sectional study with162 children: 81 with sleep problems referred for treatment (mean age: 3.67 years), matched by gender/age with 81 participants without sleep problems. Sleep problems were identified through a clinical interview with a specialist. Psychopathologies were evaluated using the Child Behavior Checklist for Ages 1.5-5 (CBCL/1.5-5).Results Having sleep problems was a predictor of all forms of psychopathologies on the CBCL scales, except for the withdrawn scale. Aggressive behavior, depression/anxiety, affective problems, and oppositional defiant disorder were associated with presence of sleep problems.Conclusion Given the probable bidirectionality of the association between sleep problems and psychopathologies in children, it is suggested that regular assessments of both phenomena should be performed in children referred for treatment of sleep problems and mental health problems in general.
Keywords: child; sleep; psychopathology; behavior